The Use of Web 2.0 Tools for Learning in EFL Context: Pre-service Teachers’ Voice - Mariska Intan Sari (Journal of Foreign Language Teaching and Learning, 2019)
Information and communication technology (ICT) has always been evolving, and its advancement has affected every aspect of human life, including education. As future teachers, pre-service teachers need to be aware of this development and have to be able to follow suit by learning how to utilize the technology for their teaching and learning processes. In English as a Foreign Language (EFL) context, Web 2.0 tools have been widely used since they provide opportunities for the users to have interaction and collaboration with other people from around the world, and, thus, open the opportunity to global learning. Therefore, this research aims to explore the Web 2.0 tools that have been employed by the pre-service teachers, and it also aims to examine the benefits they perceived in applying some of the Web 2.0 tools for their learning process in the EFL context. The results of the research show that there are five types of Web 2.0 tools that the pre-service teachers used, namely video sharing platforms, social networking tools, social photo tools, blogs, and game-based learning platforms. Concerning the benefits of using Web 2.0 tools in the learning process in the EFL context, the pre-service teachers stated that they could help them to find information more easily, allow them to collaborate with other people, enhance their language skills, and increase their motivation.